LAND ART: BRIDGING NATURE, CULTURE, AND CREATIVITY (British Journal of Global Ecology and Sustainable Development, 2024)
Land art is a contemporary artistic movement centred around creating artworks directly from natural environments or using natural elements as primary materials. This artistic direction seeks to reestablish the interconnectedness between humanity, nature, and culture. Through deliberate choices in artistic techniques and the placement of works within natural landscapes, land art serves as a poignant reflection on our relationship with the environment. This abstract explores how land art uniquely combines artistic expression with environmental consciousness, highlighting its role in fostering a deeper appreciation for the natural world and prompting critical discourse on sustainability and human impact.